(untitled) (Research, Society and Development, 2021)
In this work, the prevalence of obesity among two groups of pregnant women with diabetes will be studied, separating between those who need drug therapy and those who achieve good control with non-drug management. Gestational diabetes is the intolerance to carbohydrates first diagnosed during pregnancy. It is the most common metabolic problem during this period. Being, obesity one of the main risk factors for the development of this pathology, which generates innumerable harms for both the patient and the fetus. When diabetes is diagnosed, may be through fasting glucose numbers or by 75g OGTT test, one can obtain an adverse pregnancy outcome, requiring blood glucose regulation. For this, different strategies can be employed such as non-medication with physical exercise and balanced diet or medication with the use of oral hypoglycemic agents or insulin.